Study protocol for enhanced CJD surveillance in the 65+ years population group in Scotland: an observational neuropathological screening study of banked brain tissue donations for evidence of prion disease. Issue 10 (28th October 2019) - Peden, Alexander Howard; Kanguru, Lovney; Ritchie, Diane L; Smith, Colin; Molesworth, Anna M
Abstract : Introduction: Creutzfeldt-Jakob disease (CJD) is a human prion disease that occurs in sporadic, genetic and acquired forms. Variant CJD (vCJD) is an acquired form first identified in 1996 in the UK. To date, 178 cases of vCJD have been reported in the UK, most of which have been associated with dietary exposure to the bovine spongiform encephalopathy agent. Most vCJD cases have a young age of onset, with a median age at death of 28 years. In the UK, suspected cases of vCJD are reported to the UK National Creutzfeldt-Jakob Disease Research & Surveillance Unit (NCJDRSU). There is, however, a concern that the national surveillance system might be missing some cases of vCJD or other forms of human prion disease, particularly in the older population, perhaps because of atypical clinical presentation. This study aims to establish whether there is unrecognised prion disease in people aged 65 years and above in the Scottish population by screening banked brain tissue donated to the Edinburgh Brain Bank (EBB). Methods: Neuropathological screening of prospective and retrospective brain tissue samples is performed. This involves histopathological and immunohistochemical analysis and prion protein biochemical analysis. During the study, descriptive statistics are used to describe the study population, including the demographics and clinical, pathological and referral characteristics. Controlling for confounders, univariate and multivariate analyses will be used to compare select characteristics of newly identified suspect cases with previously confirmed cases referred to the NCJDRSU. Ethics and dissemination: Brain tissue donations to EBB are made voluntarily by the relatives of patients, with consent for use in research. The EBB has ethical approval to provide tissue samples to research projects (REC reference 16/ES/0084). The findings of this study will be disseminated in meetings, conferences, workshops and as peer-reviewed publications. Trial registration numbers: 10/S1402/69 and 10/S1402/70